Public opinion on nuclear energy and nuclear weapons: The attitudinal nexus in the United States. (October 2020) - Baron, Jonathon; Herzog, Stephen
Highlights: The use of nuclear energy in the United States is an enduring source of debate. Nuclear power's advocates and opponents often ignore links with nuclear weapons. Two studies show interdependent US public opinion on these technologies. This research supports theoretical propositions about linked nuclear attitudes. Policymakers must better understand public perceptions of this connection. Abstract: Does a lack of enthusiasm for nuclear energy among the US public relate to connections with nuclear weapons? The United States is projected to decline as the global leader in nuclear power production due to stagnation in the industry. Alongside this trend, US public skepticism of nuclear energy has remained high for decades. Policymakers, industry, and pro- and anti-nuclear advocates must understand these attitudes given electricity needs, energy sector competition, and climate change. Existing scholarship explains public opinion on nuclear power by comparing its economic and environmental desirability with other energy sources. Yet, a critical area of public opinion remains understudied: the connection between nuclear energy and nuclear weapons. Scholars have theorized such a relationship in the public consciousness, but the premise has not been systematically investigated. Two studies examine this theoretical linkage. Study 1 uses a nationally representative US survey experiment ( n = 904 ) to validate that public attitudes toward civilian and military nuclear technologies are indeed related. Study 2 uses an exploratory survey experiment ( n = 1, 003 ) to show that persuasive information about each technology affects opinion about the other. These studies provide evidence of psychological linkage. In fact, attitudes toward nuclear weapons may even drive those on nuclear energy.